Medullary thyroid cancer presenting with airway obstruction. (December 2016) - Shah, P.; Reddy, C.; Lawrence, R.; Sudarshan, P.; Wilne, S.; Daniel, M.
Abstract: A 13-year-old boy with skeletal dysplasia was found to have a subglottic cyst on oesophagogastroduodenoscopy for chronic diarrhoea. He underwent a Laryngotracheobronchoscopy, which showed a narrow subglottis. Tracheal biopsies raised the possibility of a neuroendocrine disease. CT scan showed multiple lung nodules and a thyroid mass. A diagnosis of medullary thyroid carcinoma (MTC) was made based on these findings. He underwent a tracheostomy to relieve airway obstruction and open biopsies of the thyroid were taken, all suggestive of MTC. Genetic testing showed Multiple Endocrine Neoplasia Type 2A and 2B. We discuss the unusual presentation of Medullary Thyroid Carcinoma.